Methodological and Strategic Studies in the Teaching-Learning Process of Chinese Lexicon for Spanish-Speaking Students - Sánchez Teruel, María (Sinología hispánica. China Studies Review, 2026)
Writing in Chinese characters poses considerable difficulty, which may have led both teachers and Spanish-speaking students to prioritize developing graphemic competence over lexical competence. Consequently, given the challenges of acquiring Chinese vocabulary, this article aims to analyze the teaching and learning methodologies employed to address Chinese vocabulary through two surveys targeting teachers and students. Additionally, it investigates whether mnemonic techniques and strategies are used to help achieve lexical competence, facilitating the retention of new vocabulary and aiding its transfer from short-term to long-term memory. The data obtained will provide insight into the current state of Chinese vocabulary teaching and learning in a Spanish-speaking context and contribute to the improvement of methodologies and techniques that promote the development of effective communicative competence in Chinese.